THE ISLAMIC ETHICS AND INTEGRITY IN CONCEPTUALISING ISLAMIC ACCOUNTING CONCEPTS - Norazita Marina Abdul Aziz; Fadzila Azni Ahmad (Journal of Islamic, Social, Economics and Development, 2019)
Islamic ethics can be regarded as a part of Islamic axiological stances in scrutinising the integrity and transparency issues. In line with this, the axiological stances in constructing Islamic accounting concepts involves the delineation of the moral values and ethics in securing the integrity through Islamic monitoring (hisbah). In fact, the philosophical position derives from the true knowledge founded in the Al-Quran, Hadis, Ijmak and Qiyas in bringing justice to life and the hereafter. The articulation of Islamic accounting concepts from the Islamic philosophical stances highlight the moral and ethical functions in constructing the concepts. The adherence to Shari’ah Islami’iah is a form of worship, the role of Islamic Perspective of Accounting (IPA) is thus an act of worship in fulfilling obligations to Allah (God), society and self in achieving AlFalah (rewards in this world and hereafter). The paper inductively employed qualitative as a research method in contextualising the Islamic accounting concepts within its values and principles, which can be translated within the Islamic social accountability engagement and moral imperatives. Thus, the study is conducted to provide a holistic view of the underlying ethical values and morality principles of the Shari’ah Islami’iah (Islamic teachings) to establish integrity and transparency. In line with this, the Islamic moral values and ethical conduct of an individual is essential in delineating the relationship of between man and Allah; man and another man; and lastly, man and nature (through the conception of hablum minnallah, hablum minnas). The ontological position is founded from the Tawhidic position, which underpins the concept of Oneness of the God. Parallel to this, the epistemological foundation follows the understanding of the scope of social integrity and Islamic monitoring (hisbah) as an underpinnings knowledge that may construct the evidence of tolerance, moral and ethical values within Islamic setting.